Inclusive W and Z production in the forward region at √s=7 TeV - Aaij, Roel; Adametz, Aleksandra; Bachmann, Sebastian; Bien, Alexander; Britsch, Markward; Blouw, Johan; Comerma-Montells, Albert; Dordei, Francesca; Eisele, Franz; Färber, Christian; Hansmann-Menzemer, Stephanie; Hartmann, Tobias; et al. (Journal of high energy physics, 2012)
Measurements of inclusive W and Z boson production cross-sections in pp collisions at s√=7TeVs=7TeV \sqrt {s} = 7\,{\text{TeV}} using final states containing muons are presented. The data sample corresponds to an integrated luminosity of 37 pb−1 collected with the LHCb detector. The W and Z bosons are reconstructed from muons with a transverse momentum above 20 GeV/c and pseudorapidity between 2.0 and 4.5, and, in the case of the Z cross-section, a dimuon invariant mass between 60 and 120 GeV/c2. The cross-sections are measured to be 831 ± 9 ± 27 ± 29pb for W +, 656 ± 8 ± 19 ± 23 for W − and 76.7 ± 1.7 ± 3.3 ± 2.7pb for Z, where the first uncertainty is statistical, the second is systematic and the third is due to the luminosity. Differential cross-sections, W and Z cross-section ratios and the lepton charge asymmetry are also measured in the same kinematic region. The ratios are determined to be σW+→μ+ν/σW−→μ−ν¯¯¯=1.27±0.02±0.01σW+→μ+ν/σW−→μ−ν¯=1.27±0.02±0.01 {σ_{{{W^{ + }} → {μ^{ + }}ν }}}/{σ_{{{W^{ - }} → {μ^{ - }}\overline ν }}} = 1.27± 0.02± 0.01 and (σW+→μ+ν+σW−→μ−ν¯¯¯)/σZ→μμ=19.4±0.5±0.9(σW+→μ+ν+σW−→μ−ν¯)/σZ→μμ=19.4±0.5±0.9 \left( {{σ_{{{W^{ + }} → {μ^{ + }}ν }}} + {σ_{{{W^{ - }} → {μ^{ - }}\overline ν }}}} \right)/{σ_{Z → μ μ }} = 19.4± 0.5± 0.9 . The results are in general agreement with theoretical predictions, performed at next-to-next-to-leading order in QCD using recently calculated parton distribution functions. Open image in new window
The LHCb Collaboration: R. Aaij, A. Adametz, S. Bachmann, A. Bien, J. Blouw, M. Britsch, A. Comerma-Montells, F. Dordei, F. Eisele, C. Fäber, S. Hansmann-Menzemer, T. Hartmann, A. Jaeger, K. Kreplin, G. Krocker, P. Krokovny, C. Langenbruch, C. Linn, J. Marks, M. Meissner, T. Nikodem, P. Seyfert, S. Stahl, J. v. Tilburg, U. Uwer, S. Wandernoth, D. Wiedner, A. Zhelezov [und weitere]
Gesehen am 30.10.2018